Guidance for high-dose vitamin D supplementation for prolonging the honeymoon phase in children and adolescents with new-onset type 1 diabetes - Nwosu, Benjamin Udoka (Frontiers in Endocrinology, 2022)
The publication of our recent randomized controlled trial (RCT) showing that vitamin D could protect the β-cells during the honeymoon phase of type 1 diabetes (T1D) has led to calls for guidance for vitamin D supplementation during the critical phase of type 1 diabetes. Prolonging the partial clinical remission (PR) phase of TID improves glycemic control and reduces long-term complications of T1D. This RCT randomized 36 children and adolescents to either receive vitamin D2 (ergocalciferol, given as 50,000 international units per week for 2 months and then every other week for 10 months) or a placebo. The results showed that vitamin D significantly decreased the temporal rise in both hemoglobin A1c at a mean rate of changes of 0.14% every 3 months versus 0.46% every 3 months for the placebo group (p=0.044); and in the functional marker of PR, the insulin-dose adjusted A1c at a mean rate of change of 0.30% every 3 months versus 0.77% every 3 months for the placebo group, (p=0.015). We recommend a baseline estimation of 25(OH)D concentration at the time of diagnosis of T1D, and to begin vitamin D supplementation if serum 25(OH)D concentration is <30ng/mL to maintain serum 25(OH)D concentrations between 30-60 ng/mL. If serum 25(OH)D concentration is >30ng/mL, monitor vitamin D status with serial 25(OH)D estimations; and initiate vitamin D supplementation if serum 25(OH)D concentrations drop to <30ng/mL. Continue vitamin D supplementation for at least one year to ensure optimal benefit from vitamin D supplementation during the partial clinical remission phase of T1D.